A New Heterotrophic Dinoflagellate from the North‐eastern Pacific, Protoperidinium fukuyoi: Cyst–Theca Relationship, Phylogeny, Distribution and Ecology. (19th July 2013) - Mertens, Kenneth N.; Yamaguchi, Aika; Takano, Yoshihito; Pospelova, Vera; Head, Martin J.; Radi, Taoufik; Pieńkowski, Anna J.; de Vernal, Anne; Kawami, Hisae; Matsuoka, Kazumi
Abstract: The cyst–theca relationship of Protoperidinium fukuyoi n. sp. (Dinoflagellata, Protoperidiniaceae) is established by incubating resting cysts from estuarine sediments off southern Vancouver Island, British Columbia, Canada, and San Pedro Harbor, California, USA. The cysts have a brown‐coloured wall, and are characterized by a saphopylic archeopyle comprising three apical plates, the apical pore plate and canal plate; and acuminate processes typically arranged in linear clusters. We elucidate the phylogenetic relationship of P. fukuyoi through large and small subunit (LSU and SSU) rDNA sequences, and also report the SSU of the cyst‐defined species Islandinium minutum (Harland & Reid) Head et al. 2001. Molecular phylogenetic analysis by SSU rDNA shows that both species are closely related to Protoperidinium americanum (Gran & Braarud 1935) Balech 1974. Large subunit rDNA phylogeny also supports a close relationship between P. fukuyoi and P. americanum . Three subgroups in total are further characterized within the Monovela group. The cyst of P. fukuyoi shows a wide geographical range along the coastal tropical to temperate areas of the North‐east Pacific, its distribution reflecting optimal summer sea‐surface temperatures of 14–18 °C and salinities of 22–34 psu.